Removing Polymeric Coatings With Nanostructured Fluids: Influence of Substrate, Nature of the Film, and Application Methodology - Baglioni, Michele; Alterini, Margherita; Chelazzi, David; Giorgi, Rodorico; Baglioni, Piero (Frontiers in Materials, 2019)
Cleaning is one of the most important and delicate operations in the conservation of cultural heritage, and, if not correctly performed, may irreversibly damage works of art. The removal of aged or detrimental polymeric coatings from works of art is a common operation in conservation, and nanostructured fluids (NSFs), such as aqueous swollen micelles and oil-in-water (o/w) microemulsions, are used as an alternative to non-confined organic solvents that pose a series of non-negligible drawbacks. NSFs effectiveness in removing polymeric coatings has been thoroughly demonstrated in the last decades, while their cleaning mechanism is still under investigation. The present work deepens the knowledge on the removal mechanisms of NSFs, studying the interaction of a four-component NSF with four different types of acrylic and vinyl polymer films cast from solutions or aqueous polymer latexes on three substrates (glass, marble and polystyrene) with different hydrophilicity and wettability. NSFs were applied either as non-confined or confined in cellulose poultices (traditionally employed by conservators), or in highly retentive chemical gels, observing the influence of the confining matrix on the removal process. It was found that the NSF/polymer film interaction is greatly dependent on the film structure and composition. Films formed from solvent solutions can be swollen by water/organic solvents mixtures or dewetted when a surfactant is added to the cleaning fluid; films formed from polymer latexes, on the other hand, are generally swollen even just by water alone, but poorly dewet. The substrate also plays an important role in the removal of polymer films formed from solutions, for instance the removal of an acrylic polymer from polystyrene could be achieved only through highly selective cleaning using NSF-loaded chemical hydrogels. These results can be key for conservators, providing innovative solutions to face new challenges in art preservation.